1998
DOI: 10.1023/a:1006580415796
|View full text |Cite
|
Sign up to set email alerts
|

Expression of gelatinases A and B, stromelysin-3 and matrilysin genes in breast carcinomas: clinico-pathological correlations

Abstract: The purpose of this study was to investigate the association among matrix metalloproteinases (gelatinases A and B, stromelysin-3 (ST3) and matrilysin) mRNAs expressed in primary breast carcinomas and standard prognostic parameters and clinical outcome. mRNA levels were determined by Northern analysis in samples of 81 breast cancer patients (median follow-up, 40 months) and 27 samples of uninvolved adjacent breast tissue. Proteases were expressed by the majority of the tumors and normal breast tissues examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
61
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 29 publications
8
61
0
3
Order By: Relevance
“…Previous studies on breast and lung cancers have revealed no significant correlation between the expression of MMP-7 and standard prognostic factors. 28,29 By contrast, in colorectal cancer, MMP-7 positivity in cancer cells correlates signifi- cantly with the depth of invasion, advanced Duke's stage and lymphatic and distant metastasis. 30,31 Indeed, several studies on gastrointestinal carcinomas suggest that high MMP-7 expression in cancer cells predicts shortened survival.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies on breast and lung cancers have revealed no significant correlation between the expression of MMP-7 and standard prognostic factors. 28,29 By contrast, in colorectal cancer, MMP-7 positivity in cancer cells correlates signifi- cantly with the depth of invasion, advanced Duke's stage and lymphatic and distant metastasis. 30,31 Indeed, several studies on gastrointestinal carcinomas suggest that high MMP-7 expression in cancer cells predicts shortened survival.…”
Section: Discussionmentioning
confidence: 97%
“…In melanoma, increased expression of MMP-9 is found in the early steps, but at a later stage the opposite is true (van den Oord et al, 1997). In breast and colon cancer MMP-9 expression has been correlated with both increased and decreased survival and formation of distant metastasis (Pacheco et al, 1998;Scorilas et al, 2001;Takeha et al, 1997;Zeng et al, 1996). The current view is that the gelatinases and other MMPs are needed at multiple stages during the tumor progression and different tumors may utilize different MMPs.…”
Section: Gelatinases In Tumor Progressionmentioning
confidence: 99%
“…With regard to MMP-9, many reports show that it is expressed in breast cancer tissue, but there are conflicting results regarding the identity of the cells that express this protease (Visscher et al, 1994;Heppner et al, 1996;Nielsen et al, 1996aNielsen et al, , 1997. Although the expression of MMP-9 in breast tumour tissue has been examined by different methods, namely ELISA (Duffy et al, 1995), northern blotting (Pacheco et al, 1998), zymography (Rha et al, 1997(Rha et al, , 1998, in situ hybridization (Nielsen et al, 1997) and immunohistochemistry (Nielsen et al, 1997) but to the best of our knowledge, survival analysis connecting MMP-9 expression with disease outcome has not been performed with enough samples to produce statistically significant results.…”
mentioning
confidence: 99%